Malignant Pleural Effusion: A Multidisciplinary Approach - Ana Pardessus Otero; Albert Rafecas-Codern; José M. Porcel; Pere Serra-Mitjà; Lucía Ferreiro; Maribel Botana-Rial; Cristina Ramos-Hernández; José Manuel Brenes; Lydia Canales; Valle Camacho; Beatriz Romero-Romero; Juan Carlos Trujillo; et al. (Open Respiratory Archives)
Malignant pleural effusion (MPE) has become an increasingly prevalent complication in oncological patients, negatively impacting their quality of life and casting a shadow over their prognosis. Owing to the pathophysiological mechanisms involved and the heterogeneous nature of the underlying disease, this entity is both a diagnostic and therapeutic challenge. Advances in the understanding of MPE have led to a shift in the treatment paradigm towards a more personalized approach. This article provides a comprehensive review and update on the pathophysiology of MPE and describes the diagnostic tools and the latest advances in the treatment of this complex clinical entity. Resumen: El derrame pleural maligno (DPM) se ha convertido en una complicación cada vez más prevalente en los pacientes oncológicos, empeorando la calidad de vida y ensombreciendo el pronóstico de los mismos. Debido a los mecanismos fisiopatológicos involucrados y a la naturaleza heterogénea de la enfermedad subyacente, esta entidad representa un desafío diagnóstico y terapéutico. Los avances en la comprensión del DPM han originado un cambio en el paradigma del tratamiento hacia un enfoque más personalizado. Este artículo proporciona una revisión exhaustiva y una actualización sobre la fisiopatología del DPM, y describe las herramientas diagnósticas y los últimos avances en el tratamiento de esta compleja entidad clínica.